1989
DOI: 10.1021/jm00128a024
|View full text |Cite
|
Sign up to set email alerts
|

9-Amino-1,2,3,4-tetrahydroacridin-1-ols. Synthesis and evaluation as potential Alzheimer's disease therapeutics

Abstract: The synthesis of a series of 9-amino-1,2,3,4-tetrahydroacridin-1-ols is reported. These compounds are related to 1,2,3,4-tetrahydro-9-acridinamine (THA, tacrine). They inhibit acetylcholinesterase in vitro and are active in a model that may be predictive of activity in Alzheimer's disease--the scopolamine-induced impairment of 24-h memory of a passive dark-avoidance paradigm in mice. Two compounds, (+/-)-9-amino-1,2,3,4-tetrahydroacridin-1-ol maleate (1a, HP-029) and (+/-)-9-(benzylamino)-1,2,3,4-tetrahydroacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 3 publications
1
37
0
Order By: Relevance
“…Acetylcholinesterase inhibitors continue to be the therapeutic strategy of choice for patients with Alzheimer's disease (Shutske et al, 1989;Schipchandler & Mattingly, 1990;Reisch & Gunaherath, 1993). Among the variety of acetylcholinesterase inhibitors, the acridine derivatives are one of the most efficient drugs, since they display potent action with high tolerance.…”
Section: Commentmentioning
confidence: 99%
“…Acetylcholinesterase inhibitors continue to be the therapeutic strategy of choice for patients with Alzheimer's disease (Shutske et al, 1989;Schipchandler & Mattingly, 1990;Reisch & Gunaherath, 1993). Among the variety of acetylcholinesterase inhibitors, the acridine derivatives are one of the most efficient drugs, since they display potent action with high tolerance.…”
Section: Commentmentioning
confidence: 99%
“…These two distributions were partially overlapping in the single-trial acquisition protocol. We also demonstrated that the double-trial acquisition protocol was particularly sensitive to well-known acetylcholinesterase inhibitors such as tacrine and donepezil-drugs with demonstrated efficacy against scopolamine in this test (Dawson & Iversen, 1993;Pan et al, 2006;Saxena, Singh, Agrawal, & Nath, 2008;Shutske et al, 1989). Finally, we provided evidence about the reproducibility of the behavioral performance over a period of 3 years, showing reproducible scopolamine-induced long-term-memory impairments and the prevention of such a deficit by tacrine.…”
Section: Discussionmentioning
confidence: 60%
“…As depicted in Table 3 (entries 1 and 2), cyclopentanone (10) and cycloheptanone (12), delivered a lower yield of products 11 and 13, comparative to the six-membered ring substrate cyclohexanone (Tables 1 and 2). In this regard, there was no difference with the results reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…16,18,19,21 We believe that the reaction may proceed through an initial imine-enamine tautomerism (whose preparation or isolation has been reported in some cases, depending upon the structure of the imine and enamine), activated by Lewis acid coordination under equilibrium conditions. 7,12,18,19 Next, we propose that the weakly basic nitrile of 7 is activated by Lewis acid coordination, followed by the intramolecular addition of the enamine carbon to the nitrile group to afford the intermediate 8. Next, an imine-enamine tautomerism should take place, during or prior to the alkaline hydrolysis work up, to afford 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation